AL-IMAM AL-MAHDI AL-MUNTADHAR PERSPEKTIF SUNNI SYI’AH - SYUKRI, SYUKRI (FiTUA: Jurnal Studi Islam, 2020)
Imam Mahdi is believed by both Sunni and Shiite Muslims to be present at the end of time. This belief is reinforced by the Qur'an and Sunnah of the Prophet Muhammad SAW. But they differed in their views regarding the figure of Imam Mahdi al-Muntadhar. Even among Sunnis and Shiites themselves have a variety of views. Among Sunnis there are three opinions about the Mahdi. First, Imam Mahdi comes from the descendants of Fatimah az-Zahra, whose name is the same as the name of the Prophet Muhammad. and the name of his father is the same as the name of his father the Prophet Muhammad, namely Abdullah. Secondly, Imam Mahdi is only a figure of a savior of human life. Thus, he does not have to come from the descendants of Fatimah az-Zahra, but a Muslim. Third, Imam Mahdi is not an individual figure but a symbol of the triumph of truth over evil or the triumph of justice over injustice. This assumption is widely held by modern thinkers. Among the Shiites there are also three opinions regarding the figure of the Mahdi. First, the Kaisaniyah class who considered Muhammad bin Hanafiah, the son of Ali bin Abi Talib as Imam Mahdi. Secondly, the Shia Isma'iliyah as-Sab'iyah (Shia Seven Imams) claims Isma'il bin Ja'far as-Sadiq as the Mahdi Imam. Third, the twelve Shi'ites or the Imamiyah Shiites consider the Mahdi priest to be the twelfth imam named Muhammad bin Hasan al-Mahdi. His father's name was Muhammad bin al-Hasan al-'Askari bin Imam Ali al-Hadi bin Imam Muhammad al-Jawad bin Imam Ali Ar-Ridha bin Imam Musa al-Kadzim bin Imam Ja'far Ash-Shodiq bin Imam Muhammad al-Baqir bin Imam Ali Zainal Abidin bin Imam al-Husain bin Imam Ali bin Abi Talib as. His mother was Nargis who was a spokesman.